2014
DOI: 10.1186/1471-2091-15-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum UvrD activities are downregulated by DNA-interacting compounds and its dsRNA inhibits malaria parasite growth

Abstract: BackgroundHuman malaria parasite infection and its control is a global challenge which is responsible for ~0.65 million deaths every year globally. The emergence of drug resistant malaria parasite is another challenge to fight with malaria. Enormous efforts are being made to identify suitable drug targets in order to develop newer classes of drug. Helicases play crucial roles in DNA metabolism and have been proposed as therapeutic targets for cancer therapy as well as viral and parasitic infections. Genome wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…All the effective inhibitors bind strongly to DNA [39], and so they most likely interfere with PfRuvB3 unwinding function, whose domain ought to be distant from that of ATPase. PfRuvB3 is more sensitive to daunorubicin (IC 50 of 0.76 μM) than other helicases, such as P. falciparum DNA helicase A (PfDH A) [22], P. falciparum UvrD helicase (PfUDN) [40], P. falciparum 45 kDa helicase (PfH45) [41], P. falciparum 60 kDa DNA helicase (PfDH60) [42] and human DNA helicase (HDH II) [43] (IC 50s of 2.0, 4.4, 5.0 3.0, 6.23 μM, respectively). However, it is less sensitive to netropsin (IC 50 of 7.09 μM) than PfUDN, PfH45, PfDH60 and P. falciparum Dbp5/DDX19 homolog (PfD66) [44] (IC 50s of 3.3, 0.8, 0.5, 3.2 μM, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…All the effective inhibitors bind strongly to DNA [39], and so they most likely interfere with PfRuvB3 unwinding function, whose domain ought to be distant from that of ATPase. PfRuvB3 is more sensitive to daunorubicin (IC 50 of 0.76 μM) than other helicases, such as P. falciparum DNA helicase A (PfDH A) [22], P. falciparum UvrD helicase (PfUDN) [40], P. falciparum 45 kDa helicase (PfH45) [41], P. falciparum 60 kDa DNA helicase (PfDH60) [42] and human DNA helicase (HDH II) [43] (IC 50s of 2.0, 4.4, 5.0 3.0, 6.23 μM, respectively). However, it is less sensitive to netropsin (IC 50 of 7.09 μM) than PfUDN, PfH45, PfDH60 and P. falciparum Dbp5/DDX19 homolog (PfD66) [44] (IC 50s of 3.3, 0.8, 0.5, 3.2 μM, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that helicases are plausible drug targets for malaria control . Using dsRNA‐based approaches, previous studies have shown that some helicases are crucial for the growth and survival of the malaria parasite . Furthermore, recent report suggests that the helicases most likely function in stress survival in P. falciparum .…”
Section: Plasmodium Falciparum Helicasesmentioning
confidence: 99%
“…PfUvrD is particularly expressed in the schizont stages of the intraerythrocytic development of P. falciparum 3D7 strain and it is restricted to the nucleus only . PfUvrD‐specific dsRNA inhibited the intraerythrocytic development of P. falciparum 3D7 strain suggesting that UvrD is crucial for the development of the parasite . It will be useful to identify the specific inhibitors of PfUvrD because it is parasite‐specific and required for parasite growth.…”
Section: Parasite‐specific Helicase Uvrdmentioning
confidence: 99%
“…In a recent study, P. falciparum UvrD helicase revealed that N-terminal UvrD (PfUDN) dsRNA shows inhibition in the growth of the parasite particularly during earlier phase of schizont development. The study reveals that the growth of parasite was inhibited by approximately 40% by adding PfUDN dsRNA in culture [ 114 ]. Another study observed transcriptional down-regulation of the hypusinated form of either eIF-5A or DHS upon transfection of P. berghei ANKA merozoites with eIF-5A-shRNA and DHS-shRNA, respectively, as hypusination of eIF-5A is important for cell proliferation of the parasite.…”
Section: Novel On-going Approaches To Impede Drug Resistant Malariamentioning
confidence: 99%